Does Archaeology Confirm Joseph's Time in Egypt? - Hallote, Rachel S. (The Biblical archaeology review, 2021)
The biblical story of Joseph and his brothers may have an historical basis. Is it possible that the cultural memory of the Hyksos, who ruled Egypt during the 17th and 16th centuries B.C.E. but who were later expelled, morphed into the tradition of the Israelite sojourn in Egypt and the Exodus? The history and archaeology of ancient Egypt may provide an answer.